PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK MAKANAN YANG BELUM BERSERTIFIKAT HALAL - Putri Hayuning Wulan (Fakultas Hukum Universitas Stikubank, 2019)
The development of the economy in Indonesia in the field of trade and industry has given birth to many types of goods and services. Helped with the advancement of information technology and telecommunications in Indonesia, resulting in the vast area of ​​buying and selling transactions to foreign countries. As the largest Muslim population in the world, Indonesia has the potential to become the largest producer of halal food. Business actors not only pay attention to the composition of the medical course, but also need food that is consumed legally. Legal certification of food products as a form of consumer protection against the halal of a product, not only to protect consumers but also as a bulwark to eliminate abuse authorities that harm business actors are only in the interests of consumer protection. The above is the basis for the author to take the title: